EFFECT OF OVSYNCH AND PRESYNCH PROTOCOLS ON FERTILITY AND SERUM PROGESTERONE IN REPEAT BREEDER COWS UNDER FIELD CONDITIONS - MURUGAVEL, K; HEMALATHA, H; KANTHARAJ, S; ANTOINE, D; RAJU, MS (The Indian Journal of Animal Reproduction, 2022)
Repeat breeder cows, maintained under field conditions, were inseminated at observed estrus without any treatment (control, n=15), were subjected to Ovsynch (n=13; d0 and d9 - GnRH 10 μg im; d7 - PGF2α 500 μg im; day 10 - AI 16 h after d9 GnRH) or Presynch (n=16; Two PGF2α at 14-day interval and initiating Ovsynch 12 day after the second PGF2α) protocols. The pregnancy rate on d45 post-AI for control, Ovsynch and Presynch groups were 20%, 46.1% and 37.5%, respectively. In both treatment groups, serum progesterone between pregnant (P) and non-pregnant (NP) cows at the time of first GnRH injection was similar (p>0.05). Serum progesterone on the day of AI was lower (p0.05) and on d6 post-AI was higher (p
Keywords: Conception rate; Ovsynch; Presynch; Progesterone; Repeat breeder cows